2021
DOI: 10.3390/nu13061994
|View full text |Cite
|
Sign up to set email alerts
|

Association between Bone Mineral Density and Fat Mass Independent of Lean Mass and Physical Activity in Women Aged 75 or Older

Abstract: (1) Osteoporosis and sarcopenia are frequent pathologies among the geriatric population. The interlink between these two diseases is supported by their common pathophysiology. The aim is to explore the relationship between bone mineral density (BMD) and body composition in women aged 75 or older. (2) From January 2016 to December 2019, women aged 75 or older of Caucasian ethnicity, who were addressed to perform a biphoton absorptiometry (DXA), were included in this observational study. Femoral neck T-score, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
1
0
2
Order By: Relevance
“…Sixty-three of the 66 studies reported the prevalence of osteosarcopenia. For related factors of osteosarcopenia, six studies 15,25,[28][29][30][31] reported an association between frailty and osteosarcopenia, six 16,29,[32][33][34][35] reported age, while four 16,30,34,35 reported gender and four 16,30,35,36 reported malnutrition. In terms of outcome, seven 12,[37][38][39][40][41][42] reported data on fractures, three 37,39,41 on falls, and five 14,24,37,40,43 on mortality.…”
Section: Study Summary and Patient Characteristicsmentioning
confidence: 99%
“…Sixty-three of the 66 studies reported the prevalence of osteosarcopenia. For related factors of osteosarcopenia, six studies 15,25,[28][29][30][31] reported an association between frailty and osteosarcopenia, six 16,29,[32][33][34][35] reported age, while four 16,30,34,35 reported gender and four 16,30,35,36 reported malnutrition. In terms of outcome, seven 12,[37][38][39][40][41][42] reported data on fractures, three 37,39,41 on falls, and five 14,24,37,40,43 on mortality.…”
Section: Study Summary and Patient Characteristicsmentioning
confidence: 99%
“…Gợi ý sự lắng đọng chất béo android và tỷ lệ chất béo android/gynoid không có lợi, thậm chí có thể có hại cho xương và phân bố chất béo gynoid tốt hơn android [3]. Marie Mathieu (2021), Tscore CXĐ có liên quan thuận đáng kể với khối lượng mỡ (β=0,02, 95%CI: 0,01-0,03, p<0,05) trong phân tích đa biến. Bệnh nhân giảm MĐX có khối lượng mỡ thấp hơn đáng kể (16,2 ± 6,8kg) so với (23,1 ± 10,8kg), p<0,001 [8].…”
Section: Mối Liên Quan Giữa Mđx Và Khối Mỡ Sự Phân Bố Mỡunclassified
“…Marie Mathieu (2021), Tscore CXĐ có liên quan thuận đáng kể với khối lượng mỡ (β=0,02, 95%CI: 0,01-0,03, p<0,05) trong phân tích đa biến. Bệnh nhân giảm MĐX có khối lượng mỡ thấp hơn đáng kể (16,2 ± 6,8kg) so với (23,1 ± 10,8kg), p<0,001 [8].…”
Section: Mối Liên Quan Giữa Mđx Và Khối Mỡ Sự Phân Bố Mỡunclassified